2016
DOI: 10.1093/jpids/piw005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 13-Valent Pneumococcal Conjugate Vaccine on the Serotype Distribution and Antibiotic Resistance Profiles in Children With Invasive Pneumococcal Disease

Abstract: After introduction of PCV13 in Dallas, incidence of IPD caused by strains contained in the vaccine and penicillin resistance continued to decrease. Serotype replacement phenomena and persistence of PCV7 serotypes were documented. Patients with comorbidities represented a large percentage of patients with IPD. Concerns for geographic variation in serotype replacement phenomena arise from the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Wide use of PCVs among children in many countries has contributed to a dramatic reduction in incidence of IPD ( 6 , 10 , 11 , 35 38 ), pneumonia ( 12 , 13 , 39 ), and acute otitis media ( 14 , 15 ) caused by S. pneumoniae , while providing indirect herd immunity benefits for adults ( 11 , 23 , 40 , 41 ). Replacing PCV7 with PCV13 decidedly decreased serotype 19A isolates among causative pathogens, but in several countries, NVTs such as 15A and 35B increased.…”
Section: Discussionmentioning
confidence: 99%
“…Wide use of PCVs among children in many countries has contributed to a dramatic reduction in incidence of IPD ( 6 , 10 , 11 , 35 38 ), pneumonia ( 12 , 13 , 39 ), and acute otitis media ( 14 , 15 ) caused by S. pneumoniae , while providing indirect herd immunity benefits for adults ( 11 , 23 , 40 , 41 ). Replacing PCV7 with PCV13 decidedly decreased serotype 19A isolates among causative pathogens, but in several countries, NVTs such as 15A and 35B increased.…”
Section: Discussionmentioning
confidence: 99%
“…Existing vaccines are based upon capsular polysaccharide and are highly effective only against vaccine types ( 2 5 ). Serotype replacement occurs with increased colonization and disease caused by nonvaccine strains ( 6 , 7 ). With over 90 different capsular serotypes, there is a constant race to add more capsular types to further expand coverage to reduce disease burden amid a headwind of changing strain replacement.…”
Section: Introductionmentioning
confidence: 99%
“…This finding might suggest the occurrence of competition in multi-valent vaccines such as PCV13 [54,156]. Persistence of vaccine serotypes has been noted earlier [155,157] and it has been reported that persistence and serotype replacement may have a geographical component [158]. …”
Section: Cell Wall Polysaccharides and Serotype Replacementmentioning
confidence: 84%